ANALYSIS OF FATIGUE DISORDERS IN ACTIVITIES IN FRONT OF A COMPUTER SCREEN USING A QUESTIONNAIRE ZOOM EXHAUSTION AND FATIGUE (ZEF) SCALE - Fauziah, Aswin; Kristanto, Agung; Ulfaq, Farrah Diba Ziya (Persatuan Dosen Kesehatan Masyarakat, 2025)
Human-Computer Interaction (HCI) is a discipline that studies the communication between users and systems. Initial observations revealed that 99% of Industrial Engineering students experienced fatigue due to online learning, with 85.7% reporting discomfort in areas such as the waist, neck, eyes, back, and hands. Additionally, 61.9% felt significant mental pressure. This research aims to explore the relationship between mental and physical fatigue concerning gender, Body Mass Index (BMI), daily computer usage (hours), and duration of computer use (years). The study utilized the Zoom Exhaustion and Fatigue Scale (ZEF) questionnaire to measure mental fatigue. A sample of 93 students was derived from a population of 121 active students from the 2018 and 2019 cohorts, using Slovin's formula and a 5% margin of error for accuracy. Statistical analysis employed the Chi-Square test to assess relationships between variables. Results indicated that Industrial Engineering students did not experience significant levels of mental and physical fatigue while using computers. However, a significant relationship was found between mental fatigue and daily computer usage (p = 0.052) and annual usage (p=0.039). For physical fatigue, BMI showed a significant relationship (p=0.036). Recommendations include addressing repetitive activities to prevent musculoskeletal disorders.